Activated carbon adsorption of gold from cyanide-starved glycine solutions containing copper. Part 1: Isotherms - Tauetsile, P.; Oraby, Elsayed; Eksteen, Jacques (Pergamon Press, 2019)
Cyanide-starved alkaline glycine solutions have been shown to have distinct advantages in terms of lower reagent consumption and detoxification needs, or leach rate and recovery, over cyanide- only and glycine-only leach systems respectively for gold ores with nuisance copper. Activated carbon has been shown to be suitable for gold adsorption from alkaline glycine systems, and is well established for cyanide based systems. Activated carbon being an effective substrate for the adsorption of gold thus offers a possible downstream carbon-in-pulp (CIP) recovery route for alkaline glycine leach systems and hybrid systems in the presence of cyanide. Given the frequent occurrence of gold deposits with high levels of nuisance copper, the equilibrium loading of gold and copper onto activated carbon from cyanide-starved alkaline glycine solutions containing copper and gold has been studied. Adsorption efficiency was studied in terms of equilibrium loading isotherms. Results showed that while copper adsorption is more sporadic based on goodness of fit, gold adsorption is more consistent and clearly follows the Freundlich isotherm model (good linear correlation of log Q vs log C values). The adsorption isotherms were obtained using a gold concentration of 2 ppm. In the presence of copper, the equilibrium gold loading increases with increasing glycine and calcium ion concentrations, decreases with increasing cyanide concentration and is not affected by initial gold concentration. The cuprous cyanide and cupric glycinate complexes lowered gold loading through a competitive adsorption with the copper (I) cyanide complexes adsorbing more rapidly on the carbon than their glycinate counterparts. The equilibrium gold loading capacity in cyanide-starved glycine solutions containing 2 ppm Au and 300 ppm Cu, at pH 11 was found to be 9.95 kgAu/toncarbon in 24 h, which is almost four times higher than the gold loading capacity in a pure cyanide system (2.7 kgAu/toncarbon) under similar conditions. The study revealed that activated carbon was an effective adsorbent for removal gold from cyanide-glycine aqueous solutions.